1998
DOI: 10.1056/nejm199811193392102
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Alfa-2b Alone or in Combination with Ribavirin for the Treatment of Relapse of Chronic Hepatitis C

Abstract: In patients with chronic hepatitis C who relapse after treatment with interferon, therapy with interferon and oral ribavirin results in higher rates of sustained virologic, biochemical, and histologic response than treatment with interferon alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
788
14
11

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,188 publications
(846 citation statements)
references
References 42 publications
(52 reference statements)
33
788
14
11
Order By: Relevance
“…However, the patient adamantly maintained that he was using the drug as directed. The anomalous resistance of this subject's erythrocytes to the usual deleterious effect of RBV has been observed in previous reports that found that the occasional patient receiving RBV does not experience a fall in hemoglobin [1][2][3]. The physiology underlying this resistance remains speculative.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…However, the patient adamantly maintained that he was using the drug as directed. The anomalous resistance of this subject's erythrocytes to the usual deleterious effect of RBV has been observed in previous reports that found that the occasional patient receiving RBV does not experience a fall in hemoglobin [1][2][3]. The physiology underlying this resistance remains speculative.…”
Section: Discussionmentioning
confidence: 70%
“…The complexity, radioactive exposure, and time commitment of this technique markedly reduces its clinical utility. As a result, available evidence that the anemia of RBVtreated subjects results from rapid turnover of RBCs consists solely of the demonstration of increased reticulocyte counts in some subjects [1][2][3]6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribavirin is a mutagen and inhibitor of viral RNA polymerase. 13,14 It shows antiviral activity against a variety of RNA viruses and is used to treat infections of hepatitis C virus in combination with interferon-a 15,16 and of lassa fever virus. 17 The method of using antiviral drugs might offer a novel approach for regulated SeV-mediated gene expression in primate ES cells.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The combination of ribavirin with IFN also has been shown to be effective for relapsers and nonresponders to standard IFN therapy. Efficacy has been reported to range from 29% to 49% in relapsers 12,13 and from 9.8% to 40% in nonresponders to IFN [14][15][16] ; however, in most of these studies, IFN treatment was carried out at doses of 3 million units (MU) 3 times per week. This dose is lower than that currently used in most European countries for IFN monotherapy (5 MU 3 times per week).…”
Section: Introductionmentioning
confidence: 99%